G Company's war : two personal accounts of the campaigns in Europe, 1944-1945 - Egger, Bruce E., 1923- (University of Alabama Press, 1992)
This unique account of combat in World War II provides parallel day-to-day records of the same events as seen by two men in the same company, one an enlisted man, one an officer. G Company's War is the story of a World War II rifle company in Patton's Third Army as detailed in the journals of S/Sgt. Bruce Egger and Lt. Lee M. Otts, both of G Company, 328th Regiment, 26th infantry Division. Bruce Egger arrived in France in October 1944, and Lee Otts arrived in November. Both fought for G Company through the remainder of the war. Otts was wounded seriou.
Keywords: Egger, Bruce E., -- 1923-; Otts, Lee MacMillan, -- 1922-; United States. -- Army -- Biography.; United States. -- Army. -- Infantry Regiment, 328th. -- Company G -- History.; États-Unis. -- Army -- Biographies.; United States. -- Army; United States. -- Army. -- Infantry Regiment, 328th. -- Company G; United States. -- Army. -- Infantry Regiment, 328th. -- Company G.; World War, 1939-1945 -- Campaigns -- Western Front.; World War, 1939-1945 -- Personal narratives, American.; Soldiers -- United States -- Biography.; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Front occidental.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Military -- World War II.; Military campaigns; Soldiers; United States; Western Front (World War (1939-1945)); Soldat; Erlebnisbericht; Europa; USA; Geschichte (1944-1945); 1939 - 1945; World War 2 -- Army operations; Europe; Biography; Personal Narrative; Personal narratives; Biographies; History; Personal narratives -- American; Biographies.; Personal narratives.; Récits personnels.